MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN PADA SISWA KELAS I SD NEGERI KELEYAN 1 DENGAN MENGGUNAKAN MODEL KOOPERATIF STAD: IMPROVING THE ABILITY OF BEGINNING READING IN GRADE I STUDENTS OF KELEYAN 1 ELEMENTARY SCHOOL BY USING STAD COOPERATIVE MODEL. - Perwitasari, Tsany Sahara; Setyawan, Agung (CV. Kalimasada Group, 2023)
This study was conducted with the aim of improving students' skills and learning outcomes in the Indonesian language subject of the Merdeka Curriculum by using the STAD Type Cooperative model in class 1 SD Negeri 1 Keleyan. This type of research is classroom action research (PTK). The subjects are first grade students of SD Negeri 1 Keleyan, totaling 20 students. The PTK design uses a model that includes planning, action and observation, and reflection. Data analysis used qualitative descriptive statistics. The results of the research by applying the STAD type cooperative model have improved learning outcomes in two cycles, this can be seen from the completeness of KKM, from cycle I to cycle II activities. With the results of the first cycle of reading skills completeness of 50% and learning outcomes of 50%. And in cycle II the percentage increase in reading skills reached 80%, learning outcomes 90%. The discussion method is an important method in applying the STAD Type Cooperative model, as well as the use of learning media that affects learning outcomes in research. Thus it can be concluded that the STAD Type Cooperative Model can improve the reading skills of 1st grade students of SD Negeri 1 Keleyan. Thus it can be concluded that the use of the STAD Type Cooperative model in thematic learning can improve students' skills and learning outcomes.